فاعلية ادارة المعرفة في صناعة القرار الاستراتيجي - داودي, الطيب; أحمد, بن خليفة (Recherches économiques et managériales, 2013)
تناولت هذه الدراسة موضوع مساهمة  إدارة المعرفة في تحسين صناعة القرار الاستراتيجي لعيينة من المؤسسات الاقتصادية بالوادي وهدفت إلى تأكيد دور إدارة المعرفة في تحسين صناعة القرار الاستراتيجي لقطاع المؤسسات الاقتصادية ، وكشف عن العلاقة بين إدارة المعرفة والقرار الاستراتيجي استهدفت الدراسة (36) إطار من الإدارة العليا (مدير عام ، رئيس قسم ، رئيس مصلحة) يعملون في (14) مؤسسة اقتصادية حيث جمعت البيانات عن طريق تصميم استبيان خصص جزء منه لإدارة المعرفة وتكونت من (4) متغيرات ، وخصص جزء ثاني منها للقرار الاستراتيجي الذي تفرع عنه متغيران .وقد حللت بيانات الدراسة باستخدام أساليب الإحصاء الوصفي الوسط الحسابي، الانحراف المعياري، معامل الاختلاف ، معامل الارتباط لبرسون PERSON CORRELAION واستخدام اختبار INDPENDENT SAMPLE T-TEST.          This study addresses the issue of the contribution of knowledge management to improve strategic decision-making. It is applied to a sample of economic institutions in El-Oued. It aims to confirm the role of knowledge management to improve strategic decision-making for economic institutions sector. It also aims to reveal the relationship between knowledge management and strategic decision.       The study took a sample of (36) responsibles in senior management (General Manager, Department Head, Service Chief). They work in (14) economic institutions. Data were collected through the design of a questionnaire, its first part devoted to knowledge management and consisted of (4) variables, and the second part devoted to the strategic decision which is branched into (02) variables. The data of the study is analyzed using the methods of descriptive statistics, arithmetic mean, standard deviation, coefficient of variation, correlation coefficient of Person, PERSON CORRELAION, and theuse of INDPENDEN T SAMPLE T-TES